1960
DOI: 10.1108/eb019719
|View full text |Cite
|
Sign up to set email alerts
|

STAINLESS‐STEEL CORROSION BY DILUTE NITRIC ACID: at Elevated Temperatures and Pressures

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…After a period of nine calendar years [The number of full power years (FPY) is unknown as the authors do not provide the % operation per year.] and 364 000 kW h of operation investigators reported an Fe concentration of 0?6 mg cm 23 , which corresponded to a uniform reduction in wall thickness of approximately 0?0001 in. (0?28 mm/year).…”
Section: Corrosion In Uranyl Nitrate Solutions and Simulantsmentioning
confidence: 98%
See 2 more Smart Citations
“…After a period of nine calendar years [The number of full power years (FPY) is unknown as the authors do not provide the % operation per year.] and 364 000 kW h of operation investigators reported an Fe concentration of 0?6 mg cm 23 , which corresponded to a uniform reduction in wall thickness of approximately 0?0001 in. (0?28 mm/year).…”
Section: Corrosion In Uranyl Nitrate Solutions and Simulantsmentioning
confidence: 98%
“…23 In some cases 10 g L 21 U (0?042M, presumably 238 U) was added to the solution. Exposures were conducted in both the This corresponds to a concentration that is somewhat more concentrated than the hexahydrate salt.…”
Section: Corrosion In Uranyl Nitrate Solutions and Simulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it dissociates (soluble) in weaker nitric acid to form chloride ions. This event most likely occurs in the midrange trays (8)(9)(10)(11)(12).…”
Section: Chloride Circulation Profilementioning
confidence: 99%
“…The nature of strong acids is a serious health risk and poses severe environmental threats to soil, groundwater, river and lake water, vegetation, terrestrial and aquatic organisms [11]. Temperature is also an important factor, along with the pH and oxygen level, for determining the level of crevice and pitting corrosion of a stainless steel structure [12]. Many processes within nuclear fuel manufacturing facilities operate at high temperatures.…”
Section: Introduction 11 Corrosion In the Nuclear Manufacturing Industry Overviewmentioning
confidence: 99%